Proceso de diagnóstico y evaluación psicológica de la discapacidad intelectual en la infancia, análisis de caso. - Feijoo Fernández, Isabel Jacqueline (My University, 2020)
The intellectual disability is an alteration that arises at early ages, is characterized by cognitive and adaptive restrictions, the specification is based on the severity of different levels that may correspond to mild, moderate, severe, deep, depending on the value of the individual's IQ and ability to cope with the environment; the symptomatology shows problems of language, perception, memory, motor skills, low academic performance in reading, writing, calculation, shyness, difficulty in maintaining social relationships. The purpose of this paper is to describe the process of diagnosis and psychological evaluation in case analysis of a child under 11 years old, who exhibits characteristics of the disorder. Systematic bibliographical review was carried out by means of current scientific articles referring to the topic, also information collection instruments were used such as interviews to parents, teachers, clinical history, genogram, pedagogical reports, direct and indirect observation, also the application of psychometric tests with validity and reliability indexes such as Wisc-5, K-ABC and ABAS-II is proposed, elements appropriate to the age of the subject, the integration of information from these elements originates the development of the psychological report, an instrument that is the preamble to the diagnostic approach and possible treatment with a cognitive-behavioral approach. in which the approach is posed through techniques such as psychoeducation, training in social skills, problem solving in the conceptual, social and practical domains, the therapeutic dynamic is built with support systems consisting of family, teacher, educational community, with the intention of achieving comprehensive functioning, autonomy, inclusion and quality of life.
La discapacidad intelectual es una alteración que surge en edades tempranas, se caracteriza por restricciones cognitivas y adaptativas, la especificación se basa en la gravedad de distintos niveles que pueden corresponder a leve, moderado, grave, profundo, dependiendo del valor de coeficiente intelectual del individuo y la capacidad de habituación con el medio, la sintomatología evidencia problemas de lenguaje, percepción, memoria, motricidad, bajo rendimiento académicos en lectura, escritura, cálculo, timidez, dificultad para conservar relaciones sociales. El presente trabajo tiene como propósito describir el proceso de diagnóstico y evaluación psicológica en un análisis de caso de un menor de 11 años, que exhibe características del trastorno. Se realizó revisión bibliográfica sistemática mediante artículos científicos actuales referentes al tópico, también se empleó instrumentos de recolección de información como entrevistas a padres, docentes, historia clínica, genograma, informes pedagógicos, observación directa e indirecta, asimismo se propone la aplicación de pruebas psicométricas con índices de validez y fiabilidad como Wisc-5, K-ABC y ABAS-II, elementos oportunos a la edad del sujeto, la integración de información de dichos elementos originan el desarrollo del informe psicológico, instrumento que es el preámbulo para el planteamiento diagnóstico y el posible tratamiento con enfoque cognitivo conductual; en el cual se plantea el abordaje mediante técnicas como psicoeducación, entrenamiento en habilidades sociales, resolución de problemas en los dominios conceptuales, sociales y prácticos, la dinámica terapéutica se construye con los sistemas de apoyo que consisten en familia, docente, comunidad educativa, con la intención de alcanzar el funcionamiento integral, autonomía, inclusión y calidad de vida.
Keywords: DISCAPACIDAD; INFANCIA; EVALUACION; DIAGNOSTICO